2014
DOI: 10.4236/health.2014.65043
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and its related factors among university teachers in Japan

Abstract: The purpose of this research was to investigate occupational stress and its related factors among university teachers in Japan. Questionnaire surveys were mailed to 924 university teachers in Japan with a response rate of 43.8%, N = 405. The General Health Questionnaire 28 (GHQ-28), Multidimensional Scale of Perceived Social Support (MSPSS), short Japanese version of brief Coping Orientation to Problems Experienced (COPE) and the Work Situation Questionnaires (WSQ) developed by the authors were administered to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
28
0
8

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(47 citation statements)
references
References 23 publications
5
28
0
8
Order By: Relevance
“…As job demands compromise psychological well-being among academics, it may be advisable that university administrators implement changes to policy and organizational conditions to address the issue of excessive job demands as well as enhance job resources to address the psychological and physical costs of impaired psychological health in faculty. As indicated by repeated calls by researchers in this domain (Gates, 2000;Kataoka et al, 2014;Regan et al, 2012;Zhang & Zhu, 2008), these findings similarly warrant further administrative consideration as to whether or not academics are indeed being equipped with effective strategies to combat stress. In this respect, related initiatives to develop and implement cost-effective interventions to promote academics' coping resources are needed to attenuate the adverse impact of faculty stress and negative emotions; proactive efforts to prevent damages to psychological health, as opposed to reactionary programs.…”
Section: Implications and Directions For Future Researchmentioning
confidence: 99%
“…As job demands compromise psychological well-being among academics, it may be advisable that university administrators implement changes to policy and organizational conditions to address the issue of excessive job demands as well as enhance job resources to address the psychological and physical costs of impaired psychological health in faculty. As indicated by repeated calls by researchers in this domain (Gates, 2000;Kataoka et al, 2014;Regan et al, 2012;Zhang & Zhu, 2008), these findings similarly warrant further administrative consideration as to whether or not academics are indeed being equipped with effective strategies to combat stress. In this respect, related initiatives to develop and implement cost-effective interventions to promote academics' coping resources are needed to attenuate the adverse impact of faculty stress and negative emotions; proactive efforts to prevent damages to psychological health, as opposed to reactionary programs.…”
Section: Implications and Directions For Future Researchmentioning
confidence: 99%
“…For instance, WRS costs US employers $200 billion per year [12]. Indeed, 5274 teachers were absent from Japan's schools in 2011 due to stress [13]. Moreover, the research in Ethiopia also found that nearly two thirds of teachers planned to leave the profession [14].…”
Section: Introductionmentioning
confidence: 99%
“…The findings of these studies show that certain socio-demographic characteristics e.g. age, gender, marital status, job position and work experience (Kataoka et al, 2014;Kovess-Masféty et al, 2006;Reevy & Deason, 2014) become risk factors of psychiatric morbidity among academic staff members. Apart from this, certain work related factors e.g.…”
Section: Wwwccsenetorg/iesmentioning
confidence: 99%
“…The previous research has reported similar results. For example Kataoka et al (2014) carried study on psychological health conditions of faculty members in Japan and found that symptoms of Anxiety, Depression and Social Dysfunction were prevailing among both genders, where its prevalence was high among female faculty members. Moreover, the incidence of such symptoms was high among lecturers as compared to professors.…”
Section: Prevalence Of Psychological Health Problemsmentioning
confidence: 99%
See 1 more Smart Citation